Back on Track : American Railroad Accidents and Safety, 1965-2015 - Aldrich, Mark (Book collections on Project MUSE., 2018)
"The history of American railroad safety divides into three overlapping periods. Down to roughly 1955, safety steadily improved. But as new competition arrived--cars, trucks, and airplanes--economic regulation precluded an effective response; after the mid-1950s profitability eroded and safety worsened. The focus of this book begins in 1965; the carriers were collapsing into bankruptcy and their safety eroding. Worker fatalities and grade crossing accidents increased, while train accidents skyrocketed leading to public outcry. In 1965 Congress responded with a new safety regime under the FRA and NTSB, and in 1970 it federalized all aspects of rail safety and instituted a massive grade crossing program. Despite new federal regulations, train accidents continued to increase, however. The third period begins about 1980. The carriers had been struggling to compete by providing better service and that required better safety. Aid came in 1971 as Amtrak took over money-losing passenger travel while partial economic deregulation occurred from 1976 to 1980. Freed to compete and with the funds and incentives to improve safety, the freight railroads have rapidly improved technology, cutting train and work accidents spectacularly. These were largely the result of private market incentives, for accidents were very expensive; regulation has mostly reinforced best practice. The main contributions of public policy have been support for research and development and funding for grade crossing safety. Thus, the thesis of this work is that it was not inadequate safety regulation but rather stifling economic regulation that had caused safety to collapse, while the turnaround after 1980 resulted not from tighter safety regulation but the return of more competitive railroading."--Provided by publisher